2022
DOI: 10.7324/japs.2022.121215
|View full text |Cite
|
Sign up to set email alerts
|

Murraya koenigii extract improving rate limiting enzymes on carbohydrate metabolism and GLUT-4 expression of hyperglycemic rats

Abstract: Diabetes mellitus (DM), with the main manifestation of hyperglycemia, is a metabolic disease associated with carbohydrate, protein, and fat metabolism disorders. A new treatment that can improve the activity of key enzymes in carbohydrate metabolism is promising in controlling blood glucose. Murraya koenigii (MKE) has been proven to control blood sugar in diabetic rats. This study examined MKE's performance mechanism by examining the primary enzymes' activities in carbohydrate metabolism and the glucose transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…proven to control blood sugar in diabetic rats. [54] Mahran et al showed the significant impacts of methanolic leaf powder extracts of M. koenigii and walnut against alloxan induced diabetes in murine models. [55]…”
Section: Antidiabetic Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…proven to control blood sugar in diabetic rats. [54] Mahran et al showed the significant impacts of methanolic leaf powder extracts of M. koenigii and walnut against alloxan induced diabetes in murine models. [55]…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…Found helpful in the regeneration of damaged pancreatic islet via reduction of glucose levels in plasma [130] Ethanol extract…”
Section: Reserpine-induced Orofacial Dyskinesiamentioning
confidence: 99%
See 2 more Smart Citations